Molecular systematics of South American marsh rats of the genus Holochilus (Muroidea, Cricetidae, Sigmodontinae) - D'elía, Guillermo (2015)
We present a comprehensive systematic study of Holochilus, a sigmodontine genus of large, herbivorous, and semiaquatic rodents widely distributed in South America. Remarkably, given its complex taxonomic history and large economic as well as epidemiological importance, the alpha taxonomy of Holochilus has not benefited from a molecular-based approach. The study is based on sequences of 1 mitochondrial and 3 nuclear loci that were analyzed by maximum likelihood and Bayesian inference. Analyses include sequences of specimens from localities from Argentina, Bolivia, Brazil, Colombia, Paraguay, Peru, Suriname, and Uruguay, representing all but 2 of the species currently recognized in the genus. Of the 4 data matrices, the mitochondrial data set contains the largest geographic coverage and recovered 6 species-level lineages that form 2 well-supported species groups: the brasiliensis species group formed by H. brasiliensis and H. vulpinus and the sciureus species group composed by H. chacarius, H. sciureus, and 2 currently unnamed forms. Surprisingly, in the cytochrome b gene analyses, the 2 species groups are not sister to each other; i.e., Holochilus is not monophyletic, although these topologies lack significant support. However, the monophyly of Holochilus was supported by the 3 nuclear loci as well as by the combined analysis of all 4 loci. These genealogical results are the basis of taxonomic and biogeographic considerations.